2015
DOI: 10.1039/c5ra07329d
|View full text |Cite
|
Sign up to set email alerts
|

One-class classification based authentication of peanut oils by fatty acid profiles

Abstract: Developing a method of identifying oil authenticity becomes critical for protecting customers' rights as adulteration of edible oils is a particular concern in food quality. Since adulterants in edible oils are usually unknown, the authenticity identification technique is a one-class classification model in chemometrics. In this study, a one-class classification model was built to identify the authenticity of peanut oils by fatty acid profiles. Based on the previous studies, 28 fatty acids were identified and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Traditional supervised chemometric methods lack the feature of generalizability. Previous studies have shown that fatty acid profiles could be used to identify oil types via unsupervised clustering and supervised classification 9 , 10 , 12 but these qualitative models were not directly generalizable to quantitative predictions. A recent work showed that a quantitative model for detecting two-way sesame oil mixtures showed promising results but exhibited higher errors when generalized to four-way mixtures 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional supervised chemometric methods lack the feature of generalizability. Previous studies have shown that fatty acid profiles could be used to identify oil types via unsupervised clustering and supervised classification 9 , 10 , 12 but these qualitative models were not directly generalizable to quantitative predictions. A recent work showed that a quantitative model for detecting two-way sesame oil mixtures showed promising results but exhibited higher errors when generalized to four-way mixtures 11 .…”
Section: Discussionmentioning
confidence: 99%
“…A number of chemometric methods to detect adulterated oil using fatty acid profiles has been described 9 12 . Usually these methods deal with a simple mixture of 2–3 oil types and are often qualitative in nature (e.g., PCA).…”
Section: Introductionmentioning
confidence: 99%
“…By including the information of additional classes (i.e., VOO/OO blends and EVOO with other vegetable oils), the sensitivity and specificity of the SIMCA models were 100% for all the oil classes (Table 3). Since authentication studies are often approached as a one-class classification analysis, the adulterants are usually unknown [57]. A one-class SIMCA model was developed for EVOO based on the infrared spectra of genuine samples, and any adulterated samples were classified as outliers when tested against the PCA model boundaries.…”
Section: Pattern Recognition Modeling Using Ft-ir and Raman Spectroscopymentioning
confidence: 99%
“…Food fraud, motivated by financial benefits, is a common phenomenon around the world, especially for oils, dairy products, fruit juices, honey, wine and seafood [ 1 , 2 ]. Among the food mentioned before, oil adulteration accounts for a large proportion and attracts serious attention from researchers [ 2 , 3 , 4 ]. Edible oil plays an indispensable role in our daily life as the sources of essential fatty acids, carotenoids, and lipid-soluble vitamins like vitamin E and vitamin K [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%